Visual Comparative Omics of Fungi for Plant Biomass Deconstruction - Miyauchi, Shingo; Navarro, David; Grigoriev, Igor V.; Lipzen, Anna; Riley, Robert; Chevret, Didier; Grisel, Sacha; Berrin, Jean-Guy; Henrissat, Bernard; Rosso, Marie-Noëlle (Frontiers in Microbiology, 2016)
Wood-decay fungi are able to decompose plant cell wall components such as cellulose, hemicelluloses and lignin. Such fungal capabilities may be exploited for the enhancement of directed enzymatic degradation of recalcitrant plant biomass. The comparative analysis of wood-decay fungi using a multi-omics approach gives not only new insights into the strategies for decomposing complex plant materials but also basic knowledge for the design of combinations of enzymes for biotechnological applications. We have developed an analytical workflow, Applied Biomass Conversion Design for Efficient Fungal Green Technology (ABCDEFGT), to simplify the analysis and interpretation of transcriptomic and secretomic data. The ABCDEFGT workflow is primarily constructed of self-organizing maps for grouping genes with similar transcription patterns and an overlay with secreted proteins. The ABCDEFGT workflow produces simple graphic outputs of genome-wide transcriptomes and secretomes. It enables visual inspection without a priori of the omics data, facilitating discoveries of co-regulated genes and proteins. Genome-wide omics landscapes were built with the newly sequenced fungal species Pycnoporus coccineus, Pycnoporus sanguineus, and Pycnoporus cinnabarinus grown on various carbon sources. Integration of the post-genomic data showed a global overlap, confirming the pertinence of the genome-wide approach to study the fungal biological responses to the carbon sources. Our method was compared to a recently-developed clustering method in order to assess the biological relevance of the method and ease of interpretation. Our approach provided a better biological representation of fungal behaviors. The genome-wide multi-omics strategy allowed us to determine the potential synergy of enzymes participating in the decomposition of cellulose, hemicellulose and lignin such as Lytic Polysaccharide Monooxygenases (LPMO), modular enzymes associated with a cellulose binding module (CBM1), and Class II Peroxidase isoforms co-regulated with oxido-reductases. Since enzymes active on plant biomass polymers are often members of multi-copy gene families, the strategy was particularly effective to identify the individual gene copies regulated in response to specific growth conditions. Overall, our omics data-mining platform was capable of visualizing genome-wide transcriptional and secretomic profiles for intuitive interpretations and is suitable for exploration of newly-sequenced organisms.